Stillbirth at Patan Hospital, Nepal - Shrestha, Sarada Duwal; Gurung, Padma; Shrestha, Reena; Shrestha, Prashant; Pradhan, Renee; Pant, Una (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Stillbirth (SB) is one of the most common adverse outcomes of pregnancy. The aim of this study was to determine the SB rate and to identify the likely causes contributing to SB. Methods: This cross-sectional study was conducted at Patan Hospital from 15th June 2014 to 14th June 2017 for all the cases of SBs, at or after 22 weeks, birth weight of 500 gm or more. The perinatal outcome, demographic profile, fetal characteristics, causes and contributing factors were analyzed. Results: There were 262 SB out of total 23069 deliveries, (11.24 per 1000) and 119 (46.12%) had antenatal check-up (ANC) at Patan Hospital. The 214 (82.95%) SB were among 20-34 years mothers, 133 (51.55%) being multigravida. Antepartum SB were 234 (89.31%), macerated 213 (81.30%), birth weight <1000gm 86 (32.82%) and male 156 (59.54%). The intrauterine growth restriction (IUGR) was present in 60 (22.90%), unexplained casue in 43 (16.41%), prematurity 28 (10.69%), congenital anomalies 26 (9.92%), pre-eclampsia 19 (7.25%), gestational diabetes, and abruptio placenta each 13 (4.96%). Delay in seeking care in 202 (78.30%) was a potential contributing factor. Conclusions: The SB was 11.24/1000 births. The causes in descending order were IUGR, unexplained, prematurity, congenital anomalies, pre-eclampsia, gestational diabetes and abruptio placenta. Delay in seeking care was found as a potential contributing factor.